Challenges and inclusive practices in technical and technological education in Fashion Design: a pedagogical perspective (Revista de Ensino em Artes, Moda e Design, 2025)
This study was conceived with the aim of examining the challenges and methods of inclusive teaching, with a particular emphasis on technical and technological education in clothing and fashion. The investigation analyzes how inclusion is being integrated into this domain and suggests pedagogical approaches to encourage inclusive teaching. The research is applied in nature, utilizing a qualitative approach and developed through an exploratory-descriptive lens. A bibliographic review was conducted alongside the administration of questionnaires to teachers in this field, resulting in the proposal of an inclusive practical activity. The primary results demonstrate the need for teacher training and the adoption of approaches that cater to the diverse needs of students, ensuring a more accessible educational environment.
Keywords: inclusion; apparel; teaching